The effects of artificial light at night (ALAN) on the gaping activity and feeding of mussels - Christoforou, Eleni; Dominoni, Davide; Lindström, Jan; Diamantopoulou, Christina; Czyzewski, Jakub; Mirzai, Nosrat; Spatharis, Sofie (My University, 2023)
Artificial Light at Night (ALAN) is a common environmental pollutant which affects >22 % of the world's coastlines. However, the impact of ALAN wavelengths on coastal organisms is under-investigated. Here, we tested the impact of red, green, and white ALAN on the gaping activity and phytoplankton consumption of Mytilus edulis mussels and compared these to dark night. Mussels exhibited a semi-diel activity pattern. Although ALAN did not significantly affect the time open nor the phytoplankton consumption, it did have a colour-specific effect on the gaping frequency with red and white ALAN resulting in lower activity compared to the dark night. Green ALAN caused higher gaping frequency and a negative relationship between consumption and proportion of time open compared to the other treatments. Our findings suggest colour-specific ALAN effects on mussels and call for further investigation on the associated physiological mechanisms and potential ecological consequences.
Keywords: Bivalves; Coastal pollution; Filtration; Valvometry; Wavelength